PERFORMANCE-BASED ASSESSMENTS ON STUDENTS' SPEAKING SKILLS PRACTICED BY SENIOR HIGH SCHOOL ENGLISH TEACHERS IN WEST JAVA - Yani, Gusri (2017)
Speaking is the most important language skill that students should have in order to be able to communicate in English. Performance-based assessment is an alternative assessment which makes students use and demonstrate their speaking skill directly to perform authentic speaking tasks. However, due to the complexity of performance-based speaking assessment, many teachers encountered problems while conducting the assessment; so, they become resistant to apply it. This study aimed to investigate English teachers' attitudes towards performance-based assessments on students' speaking skills and to describe how the English teachers conduct performance-based assessments to assess students' speaking skills. It is a mixed method study. The quantitative data were collected by involving 50 English teachers from fifteen senior high schools in West Java to fill out a set of questionnaires, while the qualitative data were collected through classroom observations and rubric analysis. The classroom observations were held in three of the fifteen schools. Three of the 50 teachers were chosen as the purposive sampling who were observed. The quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed using qualitative data analysis. The findings show that most of the respondents have positive attitudes towards performance-based speaking assessments, the advantages, and the principles of the speaking tasks applied in the assessments. Moreover, related to how the purposive sampling teachers conducted performance-based speaking assessments, some points need to be improved, such as the quality of the rating scales and the rubrics, the authenticity of the tasks, the frequency of the speaking assessments, and so on. It is hoped that the finding of this study can increase English teachers' understanding about the implementation of performance-based speaking assessment. Keywords: Performance-based assessment, attitude, speaking, authenticity Berbicara merupakan keterampilan berbahasa yang paling penting yang harus siswa miliki agar dapat berkomunikasi dalam Bahasa Inggris. Penilaian berbasis kinerja adalah sebuah penilaian alternatif yang membuat siswa menggunakan dan mendemonstrasikan keterampilan berbicara mereka secara langsung untuk menampilkan tugas-tugas berbicara yang autentik. Namun, karena kompleksitas penilaian keterampilan berbicara berbasis kinerja, banyak guru menghadapi masalah-masalah ketika sedang menyelenggarakan penilaian tersebut; sehingga, mereka menjadi enggan mengaplikasikannya. Penelitian ini bertujuan untuk menginvestigasi sikap guru Bahasa Inggris terhadap penilaian berbasis kinerja pada keterampilan berbicara siswa dan untuk mendeskripsikan bagaimana guru-guru Bahasa Inggris menyelenggarakan penilaian berbasis kinerja untuk menilai keterampilan berbicara siswa. Penelitian ini adalah sebuah studi metode campuran. Data kuantitatif dikumpulkan dengan melibatkan 50 guru Bahasa Inggris dari lima belas sekolah menengah atas di Jawa Barat untuk mengisi satu set kuisioner, sedangkan data kualitatif dikumpulkan melalui observasi kelas dan analisis dokumen. Observasi kelas dilakukan ditiga sekolah. Tiga dari 50 guru Bahasa Inggris dipilih sebagai sampling yang diobservasi. Data kuantitatif dianalisis dengan menggunakan statistik deskriptif, sedangkan data kualitatif dianalisis menggunakan teknik analisis data kualitatif. Temuan menunjukkan bahwa sebagian besar responden memiliki sikap positif terhadap penilaian keterampilan berbicara berbasis kinerja, keuntungannya, dan prinsip-prinsip tugas berbicara yang digunakan dalam penilaian berbasis kinerja. Selain itu, sehubungan dengan bagaimana guru Bahasa Inggris menyelenggarakan penilaian keterampilan berbicara berbasis kinerja, beberapa hal masih perlu ditingkatkan, seperti kualitas skala penilaian dan rubrik, autentisitas dari tugas-tugas, frekuensi penilaian berbicara, dan sebagainya. Harapannya, temuan dalam penelitian ini dapat meningkatkan pemahaman guru-guru tentang implementasi penilaian keterampilan berbicara berbasis kinerja. Kata-kata kunci: Penilaian berbasis kinerja, Sikap, Berbicara, Autentisitas.